To what extent do EU trade and sustainable development instruments effectively promote labour rights in the Ready-Made Garment industry of South Asia? - Peake, Katrina (2020)
This thesis analyses the extent to which EU trade and sustainable development instruments effectively promote labour rights in the Ready-Made Garment (RMG) industry of South Asia. It contextualises EU trade and sustainable development in the framework of the International Labour Organization standards, the United Nations’ Sustainable Development Goals (SDGs), predominantly SDG 8 on decent work and economic growth, and international trade law. Underpinning the research is the EU’s position as a normative actor in its external trade and development policies.